(Eco)toxicity and biodegradability of protic ionic liquids. (March 2016) - Oliveira, Maria V.S.; Vidal, Bruna T.; Melo, Claudia M.; de Miranda, Rita de C.M.; Soares, Cleide M.F.; Coutinho, João A.P.; Ventura, Sónia P.M.; Mattedi, Silvana; Lima, Álvaro S.
Abstract: Ionic liquids (ILs) are often claimed to be "environmentally friendly" compounds however, the knowledge of their potential toxicity towards different organisms and trophic levels is still limited, in particular when protic ionic liquids (PILs) are addressed. This study aims to evaluate the toxicity against various microorganisms and the biodegradability of four PILs namely, N-methyl-2-hydroxyethylammonium acetate, m-2-HEAA; N-methyl-2-hydroxyethylammonium propionate, m-2-HEAPr; N-methyl-2-hydroxyethylammonium butyrate, m-2-HEAB; and N-methyl-2-hydroxyethylammonium pentanoate, m-2-HEAP. The antimicrobial activity was determined against the two bacteria, Sthaplylococcus aureus ATCC-6533 and Escherichia coli CCT-0355; the yeast Candida albicans ATCC-76645; and the fungi Fusarium sp. LM03. The toxicity of all PILs was tested against the aquatic luminescent marine bacterium Vibrio fischeri using the Microtox ® test. The impact of the PILs was also studied regarding their effect on lettuce seeds ( Lactuta sativa ). The biodegradability of these PILs was evaluated using the ratio between the biochemical oxygen demand (BOD) and the chemical oxygen demand (COD). The results show that, in general, the elongation of the alkyl chain tends to increase the negative impact of the PILs towards the organisms and biological systems under study. According to these results, m-2-HEAA and m-2-HEAP are the less and most toxic PILs studied in this work, respectively. Additionally, all the PILs have demonstrated low biodegradability. Highlights: The toxicity and biodegradability of four PILs was tested. The elongation of the alkyl chain tends to increase the toxic effect of PILs. The PILs m-2-HEAA and m-2-HEAP are the less and the most toxic. The four PILs have low biodegradability.